Connectivity, Dependence and Strategic Leverage in Central Asia: China’s Belt and Road Initiative and the Reconfiguration of Kazakhstan’s Geopolitical Agency - Iqra Javaid; Syed Nouman Ali Shah, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
The Belt and Road Initiative (BRI) in China, launched in 2013, represents the most extensive connectivity project aimed at reshaping the geopolitical landscape of Eurasia. This research focuses on the transformation of the BRI in the changing strategic influence of China in Central Asia, with particular emphasis on Kazakhstan as the pivotal transit, energy and digital hub of the region. The study aims to determine the extent to which the BRI-related infrastructure, energy and digital networks have deepened the interdependence between China and Kazakhstan; to determine how these channels of connectivity change the geopolitical stance and agency of Kazakhstan; and to evaluate whether the BRI redefines the role of China, Russia and Western actors in Central Asia. The central research question guiding this study is: How has the BRI redefined the geopolitical stance of China and strategic autonomy of Kazakhstan in Central Asia? The connectivity depth model (CDM) is used in analysis and integrates geo-economics theories, infrastructural power and weaponized interdependence theories. Methodologically, the research follows a qualitative case study design. Triangulation of data was done using numerous sources to reduce the obscurity of the Chinese overseas financing. The findings indicate that the BRI has integrated Kazakhstan into Chinese centric transport corridors, pipes and digital systems that have generated high returns on transit efficiency, energy integration and digital modernization.